KEKERASAN TERHADAP ANAK DI KOTA PADANG - Nilam Purnama Sari; yurni suasti (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to determine the types and factors that cause child violence in the city of Padang. This study uses secondary data analysis in 2017-2018. Data collection through observation, interviews, and documentation. Data analysis uses a percentage analysis. The results showed that the dominant type of violence that occurred in Padang City was molestation in 28 cases or 67%, secondly, there were 11 cases of persecution or 26%, then online cases of the prosthesis as many as 3 cases or 7%. Factors causing child abuse consist of internal factors and external factors. Internal factors consist of parenting, family economic conditions, trauma to violence so that victims become perpetrators, as well as parents who are not intact or broken home. External factors consist of indifferent environments and unattended use of technology.